BAHASA SEBAGAI KUNCI MELAKSANAKAN GEDAN BARAI DI DOJO INKANAS AZ-ZAITUN KHOIRO BATAM - Mhd. Johan; Gaguk Rudianto; Winda Evyanto; Zia Hisni Mubarak; Yunisa Oktavia; Afriana Afriana; Dairi Sapta Rindu Simanjuntak; Robby Satria (PUAN INDONESIA, 2026)
The purpose of this service is to form the basic movements of students’ karate at Dojo Az-zaitun khoiro. Basic movements are the beginning of the formation of a karate-ka, from these basic movements the form of kata played by a karateka is seen, after that it follows into the field of the committee. When the committee is also very influential, this will be seen when you want to hit your opponent. If the punch does not match the form trained during kihon then the punch has no value. Likewise, with the form of the stand, if the stand is not correct then the movement does not get a value when the assessment process is taken, this is interrelated with each other. The method of this service is the method of providing direct training at the Az-zaitun khoiro dojo. Where the devotee directly trains the students and then tests the movements. After the test is carried out, the results of the assessment can be obtained, after an evaluation is carried out by forming the kohai-kohai movements to be better. After the kihon movement is considered good, the devotee tries to apply one movement with another movement. After it looks perfect, the material begins to be improved.